Opposite Trends in the Northern Hemisphere Stratosphere Between Mid-Winter and Early Spring Linked to Surface Temperature Anomalies - Rivière, Gwendal; D’Andrea, Fabio; Domeisen, Daniela I.V.; Portal, Alice (American Geophysical Union, 2024)
Trends in the coupled stratosphere-troposphere system during the 1979–2022 period are investigated in the Northern Hemisphere using reanalysis datasets. More upward planetary wave propagation in December is shown to precede the deceleration of the stratospheric polar vortex in January. This deceleration prevents the waves from continuing to propagate upward in February and favors an acceleration of the stratospheric polar vortex in March. This is associated with an increased Northern Hemisphere annular mode in March in the stratosphere and the troposphere. Trends show a moderate significance level because of strong interannual variability. Recent seasons whose anomalies project onto the trends are those for which wave-1 anomaly constructively interferes with wave-1 climatology in December, which occurs when there is warming in an area extending from Eastern Canada to Greenland and slight cooling over Eurasia. It shows the potential for predicting the springtime stratospheric polar vortex from wintertime wave-1 anomalies. ISSN:0094-8276 ISSN:1944-8007